Synthesis, Characterization and Antimicrobial Activity of First Row Transition Metal(II) Complexes of Novel Schiff Base Derived from Sulfapyridine and Pyridine-2-Aldehyde - Rama, I.; Usha, V. (Asian Journal of Chemistry, 2013)
A new Schiff base ligand (N-pyridin-2-yl-4-[(pyridin-2-yl)methyl amino]benzene sulfonamide) (L) was prepared by the reaction between sulfapyridine and pyridine-2-aldehyde. The ligand is bidentate by coordinating through pyridinyl nitrogen and azomethine nitrogen atom with Co(II), Ni(II), Cu(II), Zn(II) and Mn(II) chlorides. The complexes were synthesized and characterized by elemental analysis, molar conductance, magnetic moment, IR, H1 NMR and electronic spectral data. These complexes were screened in vitro antibacterial activity against the test microorganisms Staphylococcus aureus, Pseudomonas aeruginosa and fungi Candida albicans and Aspergillus niger. The results of these studies revealed that all complexes exhibit significant to moderate antimicrobial activity.